Language comprehenders are sensitive to multiple states of semantically similar objects - Horchak, O. V.; Garrido, M. V. (Journal of Memory and Language, 2024)
The present research shows that language comprehenders are sensitive to multiple states of target and semantically related objects. In Experiments 1 to 2B, participants (total N = 273) read sentences that either implied a minimal change of an object’s state (e.g., “Jane chose a mango”) or a substantial change (e.g., “Jane stepped on a mango”) and then verified whether a subsequently pictured object was mentioned in the sentence. Crucially, the picture either showed the original/modified state of an object that was mentioned in the sentence (e.g., “mango” in Experiment 1) or not (e.g., “banana” in Experiments 2A and 2B). The results of Experiment 1 demonstrated that the objects in a modified state were verified faster when a sentence implied a substantial state-change rather than a minimal state-change. In contrast, the reverse was true for the objects in the original state. Importantly, verification latencies of pictures depicting original and modified states of an object in the substantial state-change condition were approximately similar, thus suggesting that language comprehenders maintain multiple representations of an object in different states. The results of Experiments 2A and 2B revealed that when participants had to indicate that a pictured object (e.g., banana) was not mentioned in the sentence, their verification latencies were slowed down when the sentence contained a semantically related item (e.g., mango) and described this item as being changed substantially by the action. However, these verification latencies varied continuously with the degree of change: the more dissimilar the states of a semantically related item, the less time participants needed to verify a pictured object. The results are discussed through the prism of theories emphasizing dynamic views of event cognition.